The protective effect of meniscus allograft transplantation on articular cartilage: a systematic review of animal studies. Issue 8 (August 2015) - Rongen, J.J.; Hannink, G.; van Tienen, T.G.; van Luijk, J.; Hooijmans, C.R.
Summary: Despite widespread reporting on clinical results, the effect of meniscus allograft transplantation on the development of osteoarthritis is still unclear. The aim of this study was to systematically review all studies on the effect of meniscus allograft transplantation on articular cartilage in animals. Pubmed and Embase were searched for original articles concerning the effect of meniscus allograft transplantation on articular cartilage compared with both its positive (meniscectomy) and negative (either sham or non-operated) control in healthy animals. Outcome measures related to assessment of damage to articular cartilage were divided in five principal outcome categories. Standardized mean differences (SMD) were calculated and pooled to obtain an overall SMD and 95% confidence interval. 17 articles were identified, representing 14 original animal cohorts with an average timing of data collection of 24 weeks [range 4 weeks; 30 months]. Compared to a negative control, meniscus allograft transplantation caused gross macroscopic (1.45 [0.95; 1.95]), histological (3.43 [2.25; 4.61]) damage to articular cartilage, and osteoarthritic changes on radiographs (3.12 [1.42; 4.82]). Moreover, results on histomorphometrics and cartilage biomechanics are supportive of this detrimental effect on cartilage. On the other hand, meniscus allograft transplantation caused significantly less gross macroscopic (−1.19 [−1.84; −0.54]) and histological (−1.70 [−2.67; −0.74]) damage to articular cartilage when compared to meniscectomy. However, there was no difference in osteoarthritic changes on plain radiographs (0.04 [−0.48; 0.57]), and results on histomorphometrics and biomechanics did neither show a difference in effect between meniscus allograft transplantation and meniscectomy. In conclusion, although meniscus allograft transplantation does not protect articular cartilage from damage, it reduces the extent of it when compared with meniscectomy.